Alan Kaiser. Archaeology, Sexism and Scandal. The long-suppressed story of one woman’s discoveries and the man who stole credit for them. pp. 272 with ills. 2015. Lanham: Rowman & Littlefield. ISBN 978-1-4422-7524-9, paperback 28. - Haagsma, Margriet J. (Journal of Greek Archaeology, 2020)
This well-researched and very readable book tells the story of a young woman who started her professional career in Classics and Classical archaeology in the late 1920s when she enrolled as an undergraduate student in the Department of Classics at the University of Alberta, where I currently teach. It charts how, after obtaining her BA, Mary Ellingson (née Ross), was admitted as a graduate student in archaeology at Johns Hopkins University in Baltimore, Maryland, in 1931. There, she wrote an MA and PhD dissertations on the terracotta industry in Olynthus, based on the excavations in which she participated in 1931 under the guidance of the famous and distinguished David Moore Robinson, professor of archaeology and director of the Olynthus project. The author of this book, Alan Kaiser, professor in archaeology at the University of Evansville where Mary Ross-Ellingson taught for many years, became inspired to tell her story by leafing through her bequest to the university after her death. It consisted of a scrapbook, which had been sitting on a shelf in his department and in which she reports her experiences during the 1931 season at Olynthus in text and images. Based on this treasure trove of photographs and letters to family, Kaiser discovered a long known but inconvenient truth: that Mary Ross-Ellingson’s MA thesis and part of her PhD were published under Robinson’s name as volumes VII and XIV in the Olynthus series without giving credit to the real author.